Exclusão com estímulos visuais e múltiplas relações de condicionalidade na linha de base. - Oshiro, Claudia Kami Bastos (Universidade Federal de São Carlos, 2004)
This study investigated responding by exclusion , which has been demonstrated as a robust behavioral process, consisting in the selection of an undefined comparison stimulus, when the sample is also an undefined stimulus (that is, both stimuli are new in the experimental setting), without any previous history that could establish the comparison as a discriminative stimulus for the selection response. Exclusion has been extensively replicated with an experimental preparation of conditional auditory-visual discriminations in which the participant learns to relate a single sample to a single comparison. Recent research has also demonstrated the occurrence of exclusion when participants learn to relate a single name to different pictures and many names to single picture. The purpose of this study was to investigate whether exclusion would occur with visual stimuli used both as sample and comparison stimuli, without a spoken word as a nodal stimulus. Three experiments were conducted using the same experimental arrangements used in previous studies, to establish the visualvisual conditional discriminations baseline for the exclusion probes: each sample related to many comparisons (Experiment I), many samples related to each comparison (Experiment II) and a combination of both arrangements (Experiment III). In each experiment, children aged 4 to 5 years were exposed to the following experimental sequence: 1) establishment of a baseline of conditional discriminations with visual stimuli; 2) exclusion probes; 3) teaching new baseline relations; 4) additional exclusion probes; 5) probes of equivalence class formation. All children learned the conditional discriminations and showed positive results on exclusion probes and equivalence probes. The regularity observed in the data supports the conclusion that responding by exclusion occurs under a baseline of conditional discriminations including only visual stimuli, both with one-to-one pairings and many-to-one (or one-to-many) pairings. These data confirm and extend previous findings and have important implications for the comprehension of relational learning, the emergence of new behavior and the symbolic function and its role in language acquisition.
Keywords: Métodos de ensino; Controle de estímulos; Discriminação condicional; Controle por seleção; Controle por rejeição; Comportamento emergente; Exclusion; Emergent behavior; Conditional discrimination; Stimulus control topography; Control by selection; Control by rejection; Children; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL